Sound production mechanism in the semiterrestrial crab Neohelice granulata (Brachyura, Varunidae) - Sal Moyano, María Paz (2019)
Very few studies of sound production in the Brachyura have simultaneously identified the type of individuals (e.g. sex) producing acoustic signals, the structures involved in making sound and the social context. The emission and type of sound signals in Neohelice granulata were previously characterized, but the sex and the body structures involved in the sound production mechanism were not determined. In the present study, experiments conducted in the laboratory demonstrated that acoustic signals were produced by males through an up-down movement of the cheliped by rubbing the merus against the pterygostomial area of the carapace. The micromorphology of the merus showed that it has a ridge of tubercles which may act as a plectrum, while the pterygostomial area bears tubercles and might function as the pars stridens. Acoustic signals were displayed more frequently in the presence of receptive females. Agonistic encounters among males also occurred more often in the presence of receptive females. We propose that Neohelice granulata males use their chelipeds to produce sound signals in a mating context, probably to attract the receptive female and/or to repel other males when a receptive female is present. Thus, the display might have a reproductive function influencing mate choice.